Genrer og hårde data - Handesten, Lars (Passage - Tidsskrift for litteratur og kritik, 2016)
Lars Handesten: “Genre Concepts and Hard Data” The article discusses Franco Moretti’s concepts of genre, his use of data, and his notion ‘distant reading’. Moretti’s ideas are welcomed but adjusted in accordance with the genre concept suggested by Alistair Fowler. The article aims at establishing a moderated and pragmatic method for the use of quantitative research. Additionally, the concept of ‘genre literature’ is critically examined in order to make it an object of literary studies.